STRATEGI TAIWAN MENGEMBANGKAN WOLRD HALAL TOURISM (WHT) UNTUK MENARIK WISATAWAN MUSLIM INDONESIA - Sari, Wantika; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
World Halal Tourism is tourism that refers to halal destinations. world halal tourism is part of the tourism industry aimed at Muslim tourists. This study analyzes Taiwan's strategy to develop world halal tourism to attract Indonesian Muslim tourists. Taiwan's strategy is to develop halal tourism in Taiwan as a form of developing Taiwanese halal tourism and responding to the needs of Indonesian Muslim tourists during their trip to Taiwan. This study uses a constructivism perspective level analysis of the nation state strategy theory. The concept used is the concept of halal tourism. The method used is a qualitative method. Collecting data using secondary data through library research taken from books, journals and websites. This study describes the results of Taiwan's strategy to develop World Halal Tourism (WHT) to attract Indonesian Muslim tourists. The strategy carried out by Taiwan is to develop facilities that are halal and make the country Muslim Frendly. The development carried out by Taiwan can be seen from 276 halal restaurants and hotels as well as 10 mosque buildings. Taiwan's halal certification is carried out by the Chinese Muslim Association, the Taiwan Halal Integration Development Association (THIDA), the Taipei Grand Mosque Foundation by conducting an assessment and testing of the feasibility of halal tourism objects carried out directly with the Indonesian Ulema Council. Keywords : Taiwan, Strategy, Halal Tourism, Indonesian Muslim Tourists